Wages paradoxes: regional coefficient and inter-regional differentiation - E. V. Gataullina (Путеводитель предпринимателя)
The article presents the analysis of the current regional differentiation of wages, role of the regional factor in the regulation of wages, has identified paradoxes of wages in different regions of Russia, presents proposals for the forming of a «fair» coefficient of wages.